2016
DOI: 10.3892/ol.2016.5031
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative stroke in a patient undergoing surgery for oral cancer: A case report

Abstract: Abstract.Carotid artery stenosis is a significant risk factor for stroke. In elderly patients with carotid atherosclerosis and stenosis, it is not unusual for oral, head and neck cancer surgery to be performed. The present study describes a case of stroke that occurred during a neck dissection for the treatment of cervical lymph node metastasis of a left maxillary gingival carcinoma. The patient was an 84-year-old female who was considered to be at high risk of a stroke based on pre-operative head and neck com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Venous thrombosis and ischemic stroke in patients with active cancer had been reported due to cancer related hypercoagulability [2,5], and perioperative venous thrombosis and ischemic stroke had also been reported in cancer patients due to surgery related hypercoagulability [9,10]. In this case, both cancerrelated hypercoagulability and surgery-related hypercoagulability may together promote the occurrence of fatal ischemic stroke following by pulmonary embolism within 24 hours after surgery.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Venous thrombosis and ischemic stroke in patients with active cancer had been reported due to cancer related hypercoagulability [2,5], and perioperative venous thrombosis and ischemic stroke had also been reported in cancer patients due to surgery related hypercoagulability [9,10]. In this case, both cancerrelated hypercoagulability and surgery-related hypercoagulability may together promote the occurrence of fatal ischemic stroke following by pulmonary embolism within 24 hours after surgery.…”
Section: Discussionmentioning
confidence: 78%
“…Not only that, more and more studies found that DVT and ischemic stroke may occur at the same time, and together threaten life for the patient with cancer. In addition, since surgery was still one of the main therapies for cancers and anticoagulant therapy was discontinued during perioperative period, perioperative DVT and ischemic stroke, which are common complications of patients with surgical therapy and are involved surgery-related hypercoagulability [7,8], also independently or jointly lead to poor prognosis of patients with cancer [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Perioperative stroke is a cerebrovascular incident that can arise intra-operatively. A study by Sukegawa et al [ 159 ] described the case of a female patient who experienced peri-operative stroke. The authors demonstrated that there was no prophylaxis for the incidence of perioperative stroke in patients undergoing surgery for oral, neck, and head cancer.…”
Section: Effect Of Orodental Treatmentmentioning
confidence: 99%
“…Most of the histological types of oral cancer are squamous cell carcinomas. Treating oral cancer when it has already advanced in stage has been reported to have a significant impact on the patient's post-treatment quality of life and is associated with a reduced possibility of complete recovery 2 4 , which make early detection and treatment of paramount importance.…”
Section: Introductionmentioning
confidence: 99%